Enhanced Delayed Fluorescence in Nonlocal Metasurfaces: The Role of Electronic Strong Coupling - Wei, Yu-Chen; Wang, Chih-Hsing; Daskalakis, Konstantinos S.; Chou, Pi-Tai; Murai, Shunsuke; Gómez Rivas, Jaime (ACS photonics, 2025)
Strong light-matter coupling has garnered significant attention for its potential to optimize optoelectronic responses. In this study, we designed open cavities featuring nonlocal metasurfaces composed of aluminum nanoparticle arrays. The surface lattice resonances in these metasurfaces exhibit electronic strong coupling with the boron difluoride curcuminoid derivative, which is known for its highly efficient thermally activated delayed fluorescence in the near-infrared. Our results show that delayed fluorescence induced by triplet–triplet annihilation can be enhanced by a factor of 2.0–2.6 in metasurfaces that are either tuned or detuned to the molecular electronic transition. We demonstrate that delayed fluorescence enhancements in these systems primarily stem from increased absorption in the organic layer caused by the nanoparticle array, while strong coupling has negligible effects on reverse intersystem crossing rates, aligning with previous studies. We support these findings with finite-difference-time-domain simulations. This study elucidates how light-matter interactions affect delayed fluorescence, highlighting the potential applications in optoelectronic devices.